Human Adaptation in Ancient Mesoamerica: Empirical Approaches to Mesoamerican Archaeology 2015
DOI: 10.5876/9781607323921.c010
|View full text |Cite
|
Sign up to set email alerts
|

The Production, Exchange, and Consumption of Pottery Vessels during the Classic Period at Tikal, Petén, Guatemala

Abstract: Archaeological imagination [is] finding new ways of asking questions that link the most empirical of research projects with innovative social theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…While limited, paste data from sherds and provenienced whole vessels indicate that blackware was manufactured with multiple paste recipes but confined to a specific set of parameters (see references to sherd counts in Supplemental Tables 2 and 5). The most detailed come from Straight's () work at the site of Tikal in the central region. Chemical and mineralogical analyses of pastes from samples of Early Classic blackware indicate that the majority of vessels were being produced with one local clay source but that a few other sources were present, including sources from outside the Tikal geological area.…”
Section: Paste Datamentioning
confidence: 99%
“…While limited, paste data from sherds and provenienced whole vessels indicate that blackware was manufactured with multiple paste recipes but confined to a specific set of parameters (see references to sherd counts in Supplemental Tables 2 and 5). The most detailed come from Straight's () work at the site of Tikal in the central region. Chemical and mineralogical analyses of pastes from samples of Early Classic blackware indicate that the majority of vessels were being produced with one local clay source but that a few other sources were present, including sources from outside the Tikal geological area.…”
Section: Paste Datamentioning
confidence: 99%
“…Although reconstructing the organization of production and circulation of ceramics in the Maya lowlands is ongoing (Ball 1993; Bishop 1975, 2003; Bishop et al 1982; Fry and Cox 1974; Fry 1979, 1980, 2003a; McAnany 2009:199–268; Pool and Bey 2007; Rands 1967, 1969, 1987, 1988; Rands and Bishop 1980, 2003; Rice 1987a, 1987b, 1996a, 1996b, 2009; Stanton and Gallareta N. 2001; West 2003), my working hypothesis is that households of the Classic period acquired pottery through multiple provisioning strategies. At the very large Classic Maya center of Tikal, I have suggested that similar pottery forms were manufactured by fairly redundant production units (see Foias and Bishop 2007) and probably circulated through peripheral markets, among other distribution mechanisms (Straight 2012, 2014).…”
Section: Highland Tzeltal and Chuj Maya Ethnoarchaeological Datamentioning
confidence: 99%
“…Table 20 compares the vessel class frequencies from the large-scale University of Pennsylvania project at Tikal, 1955–1959, published by Fry (2003a:159, Table 5.2; 2003b: 86, Table 1) with frequencies calculated from peripheral Tikal middens by Straight (2012) and the household frequencies adapted from Aguateca (Inomata and Triadan 2010). The data from the Penn State Tikal Project (PSTP) were calculated from test pit data collected from middens at peripheral Tikal households in 2005–2006 (see Straight 2012:673–722) and serve as an independent check (and confirmation) on the previously published Tikal data. The PSTP results were calculated from rim sherds only, while the Aguateca frequencies reported represent numbers of reconstructable vessels from areal excavation.…”
Section: Relative Use-lives Of Archaeologically Recovered Vessel Classesmentioning
confidence: 99%